STUDI PUSTAKA RELEVANSI NILAI INFORMASI AKUNTANSI SEBELUM DAN SESUDAH PENERAPAN INTERNATIONAL FINANCIAL REPORTING STANDARDS (IFRS) - Baiq Reinelda Tri Yunarni (JMM UNRAM - MASTER OF MANAGEMENT JOURNAL, 2015)
This study is a reviewof the academic research on value relevance of accountinginformationafter the application of International Financial Reporting Standards (IFRS)published in The Accounting Review in period of 2008-2012. The articles in those journalhave been selected in order to be relevantwith the purpose of this study, that is to determinethe changes (increases or decreases) the value relevanceof IFRS-based accountinginformation. This study uses library research method by collecting and reviewing 27articlesto be discussed qualitatively.Overall results of the review indicate that the adoption of IFRS has not been able toincrease the value relevance of accounting information. Application of IFRS can onlyincrease the international comparability of financial statements. The review also shows thatIFRS have not been able to reduce the level of company’s earnings management.Keywords : value relevance of accounting information, IFRS adoption, The Accounting Review